Sensory and textural attributes of channa based spread - S, Keertana (Indian Journal of Dairy Science, 2016)
There are two types of spreads available in the domestic market, namely, butter and cheese spreads.Cost of butter in addition to its high-saturated fatty acids, cholesterol content, high calorific value and poor spreadability at refrigerated temperature limits its consumption.  Cheese spread, though meets all the nutritive requirements, is not so popular among Indian population because of its characteristic flavour and religious sentiments.  In this study Filled dairy spread was prepared by partial replacement of milk fat or solids with  vegetable oils or proteins. Whey powder, which is a rich source of good quality  protein, was also used in  the manufacture of dairy  spread. In the present study the  filled dairy spread  was enriched with garlic which would give a  series of health benefits.